2005
DOI: 10.4049/jimmunol.174.9.5390
|View full text |Cite
|
Sign up to set email alerts
|

Saturated and Polyunsaturated Fatty Acids Reciprocally Modulate Dendritic Cell Functions Mediated through TLR4

Abstract: TLRs provide critical signals to induce innate immune responses in APCs such as dendritic cells (DCs) that in turn link to adaptive immune responses. Results from our previous studies demonstrated that saturated fatty acids activate TLRs, whereas n-3 polyunsaturated fatty acids inhibit agonist-induced TLR activation. These results raise a significant question as to whether fatty acids differentially modulate immune responses mediated through TLR activation. The results presented in this study demonstrate that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
207
1
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 273 publications
(229 citation statements)
references
References 43 publications
17
207
1
4
Order By: Relevance
“…Dietary components and exercise can also play a role in S I and possibly in TLR4 and CCL5 [6,8,[41][42][43][44][45][46][47]. This study is too small to reliably assess the independent effect of physical activity and diet, but adjustment for changes in physical activity frequency, serum NEFA and energy-adjusted intake of total fat, saturated fat, monounsaturated fat, polyunsaturated fat or total fibre did not attenuate the independent effect of changes in waist circumference and TLR4, TLR2, TNFRSF1A or CCL5 on changes in S I (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Dietary components and exercise can also play a role in S I and possibly in TLR4 and CCL5 [6,8,[41][42][43][44][45][46][47]. This study is too small to reliably assess the independent effect of physical activity and diet, but adjustment for changes in physical activity frequency, serum NEFA and energy-adjusted intake of total fat, saturated fat, monounsaturated fat, polyunsaturated fat or total fibre did not attenuate the independent effect of changes in waist circumference and TLR4, TLR2, TNFRSF1A or CCL5 on changes in S I (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Yet dysregulation of their expression and release has been linked to excessive tissue damage and the development of insulin resistance and diabetes (28,30,41). Although it has been suggested that fatty acids can directly activate TLRs, leading to the production of cytokines, this notion is still controversial given the presence of contaminants in many BSA preparations (3,42,43). Using ultrapure BSA we observed that palmitate-treated macrophages did not release IL-1␤ or TNF␣ even through the combination of palmitate and LPS significantly stimulated the release of these cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of n-3 PUFA have been shown to involve inhibition of LPS-induced activation of NF-kB associated with decreased IkB phosphorylation (4,24) . In contrast, SFA, especially lauric acid, enhanced NF-kB activation in macrophages (4) and dendritic cells (5) and so promoted inflammatory gene expression. Lee et al (4) found that EPA and DHA, as well as other unsaturated fatty acids (arachidonic, linoleic and oleic acids), were able to prevent the pro-inflammatory effect of lauric acid in macrophages.…”
Section: Fatty Acids and Nf-kb-induced Inflammatory Gene Expressionmentioning
confidence: 99%
“…With regard to inflammation it is often considered that it is the PUFA of the n-6 and n-3 families that are most important, these often acting to oppose one another's actions (3) . However, it is now recognised that other fatty acids and fatty acid families are likely also involved in inflammation, with fairly recent work focusing on SFA (4)(5)(6) . There are a number of general mechanisms by which fatty acid exposures could affect inflammatory cell function, and so inflammatory processes.…”
Section: Proceedings Of the Nutrition Societymentioning
confidence: 99%
See 1 more Smart Citation